Microsurgical Treatment of Anterior Communicating Artery Aneurysms: An Analysis of 74 Consecutive Cases. Approach Side Choice and Outcome Considerations - Pinheiro, Leon Cleres Penido; Junior, Mario Wolak; Salgado, Joao Lucas; Neto, Francisco L. de A. Moura; Filho, Pedro Tadao Hamamoto; Zanini, Marco Antonio; Fernandes, Adriano Yacubian (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Anterior communicating artery aneurysms (ACoAAs) are intracranial aneurysms whose treatment is still considered a challenging task.Materials and Methods Altogether, 74 patients were included in this study. The variables included age, sex, comorbidities, incidence of subarachnoid hemorrhage (SAH), the Fisher, Hunt-Hess, and WFNS scores, approach side, length of hospital stay, and mortality. We also investigate A1/A2 dimensions, association with approach side choice and the influence of surgeon's experience on the outcome.Results There were 61 patients (82.2%) admitted with SAH and 13 were treated for unruptured aneurysms. The A1 and A2 branches were larger ipsilaterally to the selected approach side (p < 0,001). No deaths occurred in the unruptured aneurysm group. In the SAH group, mortality was strongly correlated with the Hunt-Hess score (p < 0.001), Fisher grade (p < 0.001), and WFNS score (p < 0.001). No significant difference was found in mortality between the right-side and the left-side approaches (p = 0.253). A significant survival difference was identified on the group operated by the senior surgeon versus the non-senior group (p = 0.048).Discussion and Conclusion A1 dominance was identified as a factor associated to the approach side for SAH cases at our center. Understanding the factors involved in brain aneurysm surgery remains a relevant and underexplored subject. Further studies involving larger case series and multicenter collaborations are necessary to elucidate these factors and to determine the external validity of our findings.
Keywords: vascular neurosurgery; anterior communicating artery aneurysm; subarachnoid hemorrhage; microsurgery